RANCANG BANGUN APLIKASI PENGARSIPAN DOKUMEN BERBASIS WEB MENGGUNAKAN METODE INCREMENTAL PADA PT. NASHTA GLOBAL UTAMA - Bagus Muhammad Saputra; Muhammad Firdaus Fitrananda; Rizal Sidik; Saparudin (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
This researcher entitled "Design and Build a Web-Based Document Archiving Application Using the Incremental Method at PT. NashTa Global Utama”. PT. NashTa Global Utama is a company founded on October 17, 2012 engaged in Information Technology Services and Procurement of Spare Parts and Software. The document filing system used today still uses traditional methods, namely in the form of physical documents stored in a cabinet and can be accessed by every individual in all divisions. The process of making this program begins by analyzing the existing systems in the company, then creating DFD, ERD and the necessary tables. Followed by designing the interface and making the program. This document archiving application uses the PHP programming language, MySQL as a database, Notepad++, Visual Studio Code as an HTML text editor. The result of this document filing system is that data search does not need to require a lot of time and effort so that the required data can be accessed quickly and easily. And the data stored is based on the provisions of each division so that data can be captured automatically based on the category so that data archiving is more effective and efficient.